Community Empowerment Through Plastic Waste Recycling To Improve Community Economy - Irdiana, Sukma; Darmawan, Kusnanto; Ariyono, Kurniawan Yunus (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
The research aims to increase people's creativity in managing plastic waste into goods that have economic value. This research raises the issue of tackling plastic waste in Lumajang Regency. The object of this research was conducted in Pasrujambe District, Lumajang Regency. This research uses a qualitative approach with a case study model. Data collection in this study used two ways, namely interviews and observations. Furthermore, after the data was collected from the informants, analysis was carried out. The results of this study indicate that the Pasrujambe community consisting of PKK, Gerbangmas and PKK Friends enthusiastically participated in the training stages. Starting from plastic waste creation training, marketing training through social media to simple accounting training. The results of this training the community can make, among others, bags, plastic drinking containers, flowers, pencil cases, vases and so on. In addition, the community has also been able to market these products through FB, WA and Instagram and the community has also benefited from the plastic waste creation products they make.